Self-Regulated Learning Strategies in Developing Growl Vocal Techniques among Metal Musicians in Bandar Lampung, Indonesia - Amelia Putri Raissyah; Prisma Tejapermana; Agung Hero Hernanda; Bian Pamungkas (Musikolastika: Jurnal Pertunjukan dan Pendidikan Musik, 2026)
Objective: This study aims to examine the self-directed learning process in mastering growl vocal techniques among metal vocalists in Bandar Lampung, focusing on learning strategies, stages of skill acquisition, and the role of the music community as a source of informal learning support. Method: A qualitative approach with a case study design was employed. Data were collected through in-depth interviews with active metal vocalists, observations of practice sessions and performances, and audio-visual documentation. Event organizers and audiences also served as additional informants to provide contextual insights into the learning process. Results and Discussion: Findings reveal that self-directed learning occurs through three structured and dynamic stages: planning, implementation, and reflection. In the planning stage, vocalists set learning goals based on auditory references and the influence of the music community, including informal mentors and fellow musicians. During the implementation stage, repeated practice is used to develop mastery of growl vocal techniques. Reflection involves self-auditory evaluation, reinforced by feedback from audiences and the music community. This approach enables vocalists to adapt techniques to their individual abilities while benefiting from social interaction within the community. Conclusion: The study confirms that mastery of growl vocal techniques can be effectively developed through self-managed learning, repeated practice, and support from the music community as an informal learning space, highlighting the importance of integrating individual practice and social interaction in extreme music education.